Prevention Of Narcotics Abuse By The Batang Kuis Police In Deli Serdang Regency - Syahputra, Rahmat Hidayat; Nurhayati, Nurhayati; Zuliah, Azmiati (Legalpreneur Journal, 2022)
The circulation and abuse of drugs in society must be prevented and tackled. This prevention effort must be carried out in accordance with the issuance of the Drug Law so that this drug problem does not continue to grow in society as a bad epidemic for the development of the country. The research methods used are normative and empirical juridical research. The nature of the research used in this study is descriptive analysis.Sources of data used in this study are primary and secondary data. The obstacles faced by the Batangkuis Police Drug Unit are 2, namely non-penal policy barriers and penal policy barriers. Based on the results of the study, the conclusion in this study is the legal regulation of narcotics based on Law No. 35 of 2009 on narcotics prioritizes rehabilitation of drug addicts and users, but very high criminal sanctions against narcotics dealers and precursors. The spirit and purpose of the promulgation of the Narcotics Act is to prevent and eradicate illicit trafficking of narcotics in Indonesia. The obstacles faced by the Batang Kuis Police Drug Unit there are two namely non-penal policy barriers and penal policy barriers.Preventive barriers related to raids carried out at night entertainment venues in Batang Kuis, often hampered by the problem of leaking information about entertainment venues to be conducted raids. The penal policy barriers faced by the Batangkuis Police Drug Unit, consists of two barriers, namely internal and external barriers.